2011
DOI: 10.1007/s12040-011-0113-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variations in outgoing long-wave radiation (OLR), convective available potential energy (CAPE) and temperature in the tropopause region over India

Abstract: Relationship of outgoing long-wave radiation (OLR) with convective available potential energy (CAPE) and temperature at the 100-hPa pressure level is examined using daily radiosonde data for a period 1980-2006.1 • E) and Kolkata (22.3 • N, 88.2 • E), and during 1989-2005 over Cochin (10 • N, 77 • E) and Trivandrum (8.5 • N, 77.0 • E), India. Correlation coefficient (R xy ) between monthly OLR and CAPE shows a significant (∼−0.45) anti-correlation at Delhi and Kolkata suggesting low OLR associated with high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The next day, April 26, 2015, also shows a high OLR value in the range of 280-290 watts/m 2 . The possibilities for enhancement in OLR are due to two reasons [52]:…”
Section: Spatial Variations Of Atmosphere and Ionosphere Parametersmentioning
confidence: 99%
“…The next day, April 26, 2015, also shows a high OLR value in the range of 280-290 watts/m 2 . The possibilities for enhancement in OLR are due to two reasons [52]:…”
Section: Spatial Variations Of Atmosphere and Ionosphere Parametersmentioning
confidence: 99%
“…Atmospheric instability/processes, mainly development of convection, can often lead to formation of clouds and precipitation, release of latent heat, etc. Several studies have reported on the seasonal and longterm variation in various atmospheric parameters such as outgoing longwave radiation (OLR), sea surface temperature (SST), precipitable water, and clouds, which have effects on convective activity over different regions (Dai 2001;Gettelman et al 2002;Ueno and Aryal 2008;Sapra et al 2011;Venkat Ratnam et al 2013). Few studies have investigated the diurnal variation in convection.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…The number of days with OLR ≤ 180 W m ‐2 is closely related to the number of days with precipitation ≥10 mm (Sandeep and Strodal, ). The relationship among OLR, convective available potential energy and temperature was examined at the 100 hPa pressure level over Delhi, Kolkata, Cochin and Trivandrum, India (Sapra et al, ) and observed a positive correlation between OLR and temperature at Delhi and Kolkata. On the other hand, an investigation was carried out on the association between mid‐latitude circulations and rainfall over Indian region on an intra‐seasonal timescale by considering 11 years (1974–1984) of Northern Hemisphere 500 hPa geo‐potential height and rainfall data for Indian summer monsoon months (Kriplani et al, ).…”
Section: Introductionmentioning
confidence: 99%